2017
DOI: 10.3897/mycokeys.22.13083
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma sichuanense (Ganodermataceae, Polyporales) new to Thailand

Abstract: Ganoderma sichuanense (Ganodermataceae) is a medicinal mushroom originally described from China and previously confused with G. lucidum. It has been widely used as traditional medicine in Asia since it has potential nutritional and therapeutic values. We collected 8 specimens of Ganoderma species from Thailand and show that they represent the first record of G. sichuanenese for Thailand. In this paper, we describe our specimens of Ganoderma sichuanense based on fresh basidiomes, and provide line drawings and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
1
16
0
3
Order By: Relevance
“…material 5: Fig. S2c) is closely related to G. lingzhi in agreement with previous phylogenies (Zhou et al 2015;Thawthong et al 2017). It occurs in North America -being widespread in the eastern parts of the USA -primarily on angiosperms.…”
Section: Clade a -Cluster A3supporting
confidence: 88%
“…material 5: Fig. S2c) is closely related to G. lingzhi in agreement with previous phylogenies (Zhou et al 2015;Thawthong et al 2017). It occurs in North America -being widespread in the eastern parts of the USA -primarily on angiosperms.…”
Section: Clade a -Cluster A3supporting
confidence: 88%
“…Several reports have confirmed that this fungus is mentioned in Hainan Province polypore diversity checklists [13,61,120,121]. This fungus is distinctive in these forms, featuring a laccate pileus with broadly ellipsoid basidiospores with double walls, and it is widely found across subtropical and tropical Asia [108,119,122]. Wang and Wu [112] suggested that G. calidophilum is a synonym of G. flexipes.…”
Section: Taxonomymentioning
confidence: 91%
“…Notes: Ganoderma australe belongs under the subgenus Elfvingia [38]. This fungus was initially described from the Pacific Islands [108]. G. australe belongs to the G. applanatumaustrale complex [2].…”
Section: Taxonomymentioning
confidence: 99%
“…Taxonomic and phylogenetic studies of Ganodermataceae have been carried out in recent years, but most studies focused on Ganoderma ( Smith & Sivasithamparam 2000 , Hong & Jung 2004 , Pilotti et al 2004 , Wang et al 2009 , Cao et al 2012 , Cao & Yuan 2013 , Li et al 2014b , Lima Júnior et al 2014 , Coetzee et al 2015 , Hapuarachchi et al 2015 , Xing et al 2016 , Xing et al 2018 , Thawthong et al 2017 ) and only a few studies dealt with Amauroderma ( Gomes-Silva et al 2015 , Costa-Rezende et al 2016 , 2017 , Song et al 2016 ). Regarding this phylogenetic context, Amauroderma has been pointed as polyphyletic and regarded as Amauroderma s.lat., in which Amauroderma s.str.…”
Section: Introductionmentioning
confidence: 99%